Neuropeptides SP and CGRP Underlie the Electrical Properties of Acupoints - Fan, Yu; Kim, Do-Hee; Ryu, Yeonhee; Chang, Suchan; Lee, Bong Hyo; Yang, Chae Ha; Kim, Hee Young (Frontiers in Neuroscience, 2018)
Electrical skin measurements at acupuncture points (acupoints) have been utilized as a diagnostic and therapeutic aid for more than 50 years. Although acupoints are described as having distinct electrical properties, such as high conductance and low impedance, the underlying mechanisms are currently unknown. The present study investigated in a rat model of hypertension whether the high conductance at acupoints is a result of the release of the neuropeptides substance P (SP) and calcitonin gene-related peptide (CGRP) during neurogenic inflammation in the referred pain area. When plasma extravasation from neurogenic inflammation was examined by exploring the leakage of intravenously injected Evans blue dye (EBD) to the skin, extravasated EBD was found most frequently in acupoints on the wrist. The increased conductance and temperature at these acupoints occurred during the development of hypertension. The increase in conductance and plasma extravasation at acupoints in hypertensive rats was ablated by cutting median and ulnar nerves, blocking small diameter afferent fibers with resiniferatoxin (RTX) injection into median and ulnar nerves, or antagonizing SP or CGRP receptors in acupoints. In turn, intradermal injection of SP or CGRP resulted in increased conductance and plasma extravasation in naïve rats. Elevated levels of SP and CGRP were found in the acupoints of hypertensive rats. These findings suggest that the high conductance at acupoints is due to vascular leakage following local release of SP and CGRP during neurogenic inflammation.